The effect on participation rates of including focused spirometry information in a health check invitation: a cluster-randomised trial in Denmark - Lene Maria Ørts; Anders Løkke; Anne-Louise Bjerregaard; Helle Terkildsen Maindal; Kasper Norman; Bodil Hammer Bech; Annelli Sandbæk (BMC, 2019)
Abstract Background Early detection of lung disease may help reduce disease development. Detection through preventive health checks may be beneficial. Nevertheless, the knowledge is sparse on how to enhance the participation rate in health checks among citizens at risk of developing lung disease. This study investigates if focused information on spirometry can increase the participation rate in a general health check. Methods We conducted an open-label, household cluster-randomised trial with a two-group parallel design including 4407 citizens aged 30-49 years in Denmark and an average cluster size of 1.55 citizens per household. The control group (n = 2213) received a standard invitation describing the content of the general health check and containing practical information. The intervention group (n = 2194) received an extended invitation highlighting the benefits of early detection and prevention of lung disease. The primary outcome was difference in participation rate between the two groups. The secondary outcome was the proportion of participants at risk of lung disease in both groups. Risk profile was defined as current smoking or self-reported lung symptoms. The inclusion period was 25 November 2015-3 February 2017. Results No major difference in participation rate was seen between the intervention group (53.4%) and the control group (52.0%). Participants had statistically significantly higher education level compared to non-participants. A total of 24.2% of the participants were at risk of developing lung disease, but no difference was found between the intervention group and the control group. Conclusion This study revealed no effect on participation rate of including focused spirometry information in the health check invitation. Trial registration ClinicalTrials.gov: NCT02615769. Registered on 25 November 2015. The trial protocol has been published.